Histopathology of Psoriatic Arthritis Synovium—A Narrative Review - Tenazinha, Catarina; Barros, Rita; Fonseca, João Eurico; Vieira-Sousa, Elsa (Frontiers in Medicine, 2022)
Psoriatic Arthritis (PsA) is a phenotypically heterogeneous chronic inflammatory disease associated to type I major histocompatibility complex alleles whose complex pathogenesis is still not completely understood. The psoriatic synovium shares general features of chronic inflammation with Rheumatoid Arthritis (RA) and other arthritis, such as hyperplasia of the intimal lining layer, sublining influx of inflammatory cells and neoangiogenesis, but recognising disease-specific histopathologic findings may help in diagnosis and definition of therapeutic targets. Available literature reports conflicting data regarding the extension of lining hyperplasia, that does not allow depiction from RA. Sublining inflammatory cells consist of T and B cells and macrophages, plasma cells, mast cells and follicular dendritic cells, with a higher amount of overall T, mast cell and IL17 producing CD8+ T lymphocytes and lower proportion of plasma cells when compared to the rheumatoid synovium. The amount of synovium IL17+CD8+ T cells correlates positively to measures of disease activity. Lymphoid follicles with characteristics of germinal centres have been identified, similar to the ones described in RA. Neoangiogenesis is more prominent in PsA but can also be an outstanding feature in some RA samples, and different molecules involved in the process appear to have different influence in each disease. IL17 and IL22 expression in the synovium does not allow depiction between diseases. Among other cyotokines and molecules likely implicated in disease physiopathology, only IL-35 is demonstrated to be reduced in PsA when compared to RA.